Negative stereotypes towards ageing in college students majoring in the health field - Lara-Pérez, Ricardo (Universidad de Sonora, 2019)
Introduction: Negative stereotypes towards ageing generate discriminatory behavior (ageism) toward older adults. Objective: Analyze the presence and intensity of the negative stereotypes towards ageing present within the students within the Health Department of the Universidad de Guanajuato (UGTO by its acronym in Spanish). Methodology: Quantitative, descriptive, cross-sectional, and comparative study; stratified sampling of n=326 students registered in the August-December period. Application of the Evaluation Questionnaire of Negative Stereotypes towards Ageing (CENVE by its acronym in Spanish), whose point scale ranges between 15 and 60 points, greater punctuation an elevated degree of negative stereotypes against ageing. Descriptive statistics were used for categorical variables by distribution of frequencies and percentages, and for numeric variables, measures of central tendency and dispersion. Results: Average age of 20.15±1.67 years; female gender was predominant (79.9%); CENVE score of 36.24±4.96; the most affected dimension was that of Character-Personality. There exists a presence of negative stereotypes within 37% of the cases, no differences existed between the groups. The presence of negative stereotypes was greater in comparison to South American studies; likewise, the CENVE score was greater than those obtained in studies performed in Spain and Costa Rica. The most affected dimension differs in regards to international and national studies where the most affected dimension is health. Conclusions: Elevated negative stereotypes prevail within the population studied; the most affected dimension was that of Character-Personality. The implementation of programs starting on basic education is recommended, programs favoring socio-emotional skill-building that serve to decrease ageism.